The relationship between fatigue level and dyspnea in post-COVID-19 patients - Ali Multazam; Herlianti; Nurul Aini Rahmawati (Physical Therapy Journal of Indonesia, 2023)
Background: Post-coronavirus disease 2019 (Post-covid-19) is a term used to describe people with COVID-19 symptoms that persist after two weeks from the onset of symptoms. Some of the most common post covid-19 symptoms are fatigue and dyspnea. Fatigue is a feeling of physical or mental debilitation resulting from a person's immune and psychological changes. Breathing becomes faster and shorter when insufficient oxygen reaches the lungs, a condition known as dyspnea. Methods: This study used the cross-sectional design. The population of this study consisted of post-COVID-19 patients who live in Malang Raya, with a sample size of 56 respondents. Data collection using the Fatigue Severity Scale questionnaire to measure fatigue levels and the Borg Scale to measure dyspnea levels. Results: The results of Spearman's test obtained a value of r= 0.498, with a moderate correlation, indicating there was a relationship between the level of fatigue and dyspnea. Conclusion: There was a relationship between fatigue level and dyspnea in post-COVID-19 patients.